Analysis of the current electric motor market in Ukraine: formation, assessment, perspectives - Proskurnia, Olena; Boiko , Nikita; Synihovets , Olha (Management and Entrepreneurship: Trends of Development, 2025)
This article presents a comprehensive analysis of the current electric motor market in Ukraine, what is the object of research, covering its formation, major trends, assessment of the current status, and development prospects. Special emphasis is placed on the impact of economic factors and global trends on the market structure and competitiveness. The role of domestic manufacturers, import partners, and consumers in shaping supply and demand for electric motors is examined. The impact of martial law on the electric motor market in Ukraine has been studied, which is manifested in a sharp drop in the total market volume (by ~50% in 2022); an increase in prices (over 30%); a decrease in the share of the domestic manufacturer (up to 70%). A cardinal change in the demand structure in favor of the defense sector is also observed. Key areas for further sector development are identified. The findings aim to support businesses, and researchers in making strategic decisions amid rapid economic and technological transformations. The research methodology was a comprehensive analysis of statistical data for the period from 2019 to 2024, which are freely available. Thus, the subject of research became statistical data that characterize the electric motor market and its changes. The study examines the economic condition of the industry, analyses domestic and foreign manufacturers, and assesses the structure of domestic consumption of the electric motor. We analysed the development trajectory of the industry and the growth potential of this sector of the national economy. The scientific significance of the work lies in its ability to inform and improve promising investment projects aimed at developing the electric motor market and restoring the industry. The value of the study lies in the fact that it emphasises the importance of attracting international grants and implementing comprehensive state policies that must be implemented with a long-term perspective.JEL Classification L10, L68, O40.